Capacity development through international projects: a complex adaptive systems perspective. Issue 3 (6th June 2016) - McEvoy, Peter; Brady, Malcolm; Munck, Ronaldo
Abstract : Purpose: – International development practice has had as its dominant paradigm the rational-analytic model of project planning, management and evaluation. This is reflected in the widespread adoption by donor agencies of results-based management (RBM), side by side with conventionally used tools for monitoring and evaluation (including logical framework analysis ("logframe"), logic model and results frameworks). Donor agencies rely upon such tools to generate the evidence base for measuring "success" across the spectrum of their work, even though projects differ enormously in their nature, scope and time-span. Process-led capacity development projects and input-led infrastructural or straightforward service delivery projects require very different yardsticks of performance monitoring and appraisal. Drawing on insights from the complex adaptive systems (CAS) literature, the purpose of this paper is to explore how projects focused on capacity development necessitate a more eclectic approach, including – but not restricted to – RBM methodology. Design/methodology/approach: – Using the insights of CAS theory, and with particular reference to projects which have capacity development as their prime focus, this paper explores a broadening of conventional project management practices. Findings: – The paper posits an integrative approach to managing international development projects focused on capacity development – one which would recognise the values of instrumental utility and goal-setting associated with the application of the tools of RBM, while situating that within a more open, system focused and holistic approach to projects and their outcomes, placing emphasis on context, adaptability and learning. Research limitations/implications: – The research enquiry presented is discursive rather than empirical, and builds on established theory and constructs of three distinct conceptual fields: first, the RBM approach to project and programme implementation; second, the "complexity" strand of organisational management literature; and third, the capacity development strand of international development discourse. Originality/value: – The paper intersects disciplinary boundaries between project management, organisational studies and international development theory and practice.